The Japanese Military and the Burma Independence Army in Northern Thailand, 1939-1942 - Apiwong, Thanyarat (Thai Journal of East Asian Studies, 2018)
This article examines the cooperation between the Japanese military and Burmese nationalists in Thailand in establishing the Burma Independence Army (BIA) in Thailand during the Second World War. It focuses on the role of the Japanese military and Burmese nationalists who lived in Northern Thailand, which hosted numerous Burmese migrants. This study found that the Japanese military in Thailand attempted to inflame a sense of Burmese nationalism and to use the same strategies as they had used in British Burma in order to recruit Burmese migrants for the BIA. The problem of recruiting Burmese migrants was that their sense of Burmese nationalism was not as strong as the Burmese who lived in British Burma. For this reason, the Japanese military not only turned to Burmese monks and the social networks of local Burmese nationalists to persuade local Burmese to join the BIA but also made use of the legal status of British Burmese subjects in order to increase the number of those conscripted.